Collection of Gender Identity in National Case Notifications of Chlamydia, Gonorrhea, and Primary and Secondary Syphilis, 2018. Issue 9 (September 2020) - Torrone, Elizabeth; Grier, LaZetta; Gadsden-Knowles, Kim; Weinstock, Hillard; Stenger, Mark
Abstract : Abstract: In 2018, 21 (41%) jurisdictions had begun reporting gender identity for sexually transmitted disease case notifications sent to the Centers for Disease Control and Prevention. Among jurisdictions with ≥70% of cases with reported gender identity and sex, 1.0% of primary and secondary syphilis cases were identified as transgender and 71% of transgender women with syphilis were concurrently coded as being male sex. Abstract : We reviewed national case reports of chlamydia, gonorrhea, and primary and secondary syphilis to describe progress toward the collection of gender identity and estimate the distribution of cases by gender identity.Supplemental digital content is available in the text.